Growing flowers for seed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Moses Kilusu grows ornamental flowers in order to harvest their seed, on his farm near Arusha in Tanzania. He works under contract to the Multiflower company.